A one health perspective for integrated human and animal sanitation, nutrient recycling and climate change - Hung Nguyen-Viet; Cissé, G.; Phuc Pham-Duc; Vi Nguyen; Tanner, M.; Odermatt, P.; Tu Vu-Van; Hoang Van Minh; Zurbrugg, C.; Schelling, E.; Zinsstag, Jakob (CAB International, 2021)
In this chapter, the authors present their experiences in developing a conceptual framework for integrated health and environmental assessment, combining health status, physical, socio-economic and cultural environments to improve health and minimize environmental impact. Highlights focused on how the framework was used to manage human and animal excreta in Vietnam and the added value offered from an integrated assessment.